Differential Effects of Varying Concentrations of Phosphorus, Iron, and Nitrogen in N2-Fixing Cyanobacteria - Fernández-Juárez, Víctor; Bennasar-Figueras, Antoni; Sureda-Gomila, Antoni; Ramis-Munar, Guillem; Agawin, Nona S. R. (Frontiers in Microbiology, 2020)
Diazotrophs or N2-fixers are one of the most ecologically significant groups in marine ecosystems (pelagic and benthic). Inorganic phosphorus (PO43–) and iron (Fe) can limit the growth and N2-fixing capacities of cyanobacteria. However, studies investigating co-limitation of these factors are lacking. Here, we added different concentrations of PO43– and Fe in two cyanobacterial species whose relatives can be found in seagrass habitats: the unicellular Halothece sp. (PCC 7418) and the filamentous Fischerella muscicola (PCC 73103), grown under different nitrate (NO3–) concentrations and under N2 as sole N source, respectively. Their growth, pigment content, N2-fixation rates, oxidative stress responses, and morphological and cellular changes were investigated. Our results show a serial limitation of NO3– and PO43– (with NO3– as the primary limiting nutrient) for Halothece sp. Simultaneous co-limitation of PO43– and Fe was found for both species tested, and high levels of Fe (especially when added with high PO43– levels) inhibited the growth of Halothece sp. Nutrient limitation (PO43–, Fe, and/or NO3–) enhanced oxidative stress responses, morphological changes, and apoptosis. Furthermore, an extensive bio-informatic analysis describing the predicted Pho, Fur, and NtcA regulons (involved in the survival of cells to P, Fe, and N limitation) was made using the complete genome of Halothece sp. as a model, showing the potential of this strain to adapt to different nutrient regimes (P, Fe, or N).